2014
DOI: 10.1002/aic.14573
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism and kinetic modeling for steam reforming of toluene on La0.8Sr0.2Ni0.8Fe0.2O3 catalyst

Abstract: Reaction mechanism for steam reforming of toluene is proposed for La0.8Sr0.2Ni0.8Fe0.2O3 perovskite catalyst. The proposed mechanism was derived from various characterization results such as temperature‐programmed desorption (TPD) and temperature‐programmed surface reaction (TPSR) water, TPSR toluene, TPD O2 and in situ DRIFT of toluene decomposition, and steam reforming of toluene. Five kinetic models were developed based on the proposed dual‐site reaction mechanism using Langmuir–Hinshelwood approach. Subseq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
2
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 89 publications
(38 citation statements)
references
References 60 publications
0
33
2
2
Order By: Relevance
“…The schematic of the setup was reported in our previous studies [26,34,35]. Briefly, the inlet section consisted of a specific concentration of To eliminate the mass-transfer effect, we selected a sample size of 100-150 mesh by providing the catalyst bed height to a catalyst particle size ratio of L/D p ≥ 50 and reactor internal diameter to a catalyst particle size ratio of D/D p ≥ 30 [36]. Catalytic ozonation of gaseous toluene over the MnO 2 /graphene sample was performed at varied temperatures (295, 313, and 333 K) under atmospheric pressure.…”
Section: Steady-state Kinetic Studymentioning
confidence: 99%
“…The schematic of the setup was reported in our previous studies [26,34,35]. Briefly, the inlet section consisted of a specific concentration of To eliminate the mass-transfer effect, we selected a sample size of 100-150 mesh by providing the catalyst bed height to a catalyst particle size ratio of L/D p ≥ 50 and reactor internal diameter to a catalyst particle size ratio of D/D p ≥ 30 [36]. Catalytic ozonation of gaseous toluene over the MnO 2 /graphene sample was performed at varied temperatures (295, 313, and 333 K) under atmospheric pressure.…”
Section: Steady-state Kinetic Studymentioning
confidence: 99%
“…However, for NSL catalysts, some of the Sr is located between the Ni and the La 2 O 3 support, resulting in stronger interaction between the Ni and La 2 O 3 support. Our previous study 11,12 reported that Sr can adsorb and desorb more water at higher temperature than La, but only La can activate the water. Therefore, this study shows that the crucial role of Sr to strongly adsorb and desorb water can be enhanced by arranging Sr on the catalyst surface.…”
Section: Xps Of Reduced Catalystsmentioning
confidence: 99%
“…Oxygen affinity of Ce improved the activity of Ni/Al 2 O 3 catalyst in terms of coke suppression. Adsorbed O species in presence of Ce and Ni, due to lattice O and redox properties of Ce forms gas species such as CO 2 and CO instead of coke deposition (Oemar et al, 2014). Fig.…”
Section: Effect Of Catalysts On Product Distributionmentioning
confidence: 99%